2019
DOI: 10.1002/hep.30893
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Mediated Inhibition of miR‐181c Activates ATM Signaling and Promotes Hepatocyte Growth

Abstract: Background and Aims Hepatitis C virus (HCV) infection promotes hepatocyte growth and progress to hepatocellular carcinoma. We previously observed that HCV infection of hepatocytes transcriptionally down‐regulates miR‐181c expression through CCAAT/enhancer binding protein β (C/EBP‐β). Here, we examined the role of miR‐181c in the regulation of cell cycle progression in relation to HCV infection. In silico analysis suggested that ataxia‐telangiectasia mutated (ATM) protein, a protein kinase, is a direct target o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
2
10
1
Order By: Relevance
“…A number of studies also reported that miR‐181c was downregulated in late stages of fibrosis. However, these studies reported that miR‐181c was downregulated in HCV patients compared with controls that disagrees with our finding 30,31 . This discrepancy between our result and others regarding miR‐181c may occurred because the other studies included patients infected with genotype‐1a and genotype‐2a HCV that have specific genome.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of studies also reported that miR‐181c was downregulated in late stages of fibrosis. However, these studies reported that miR‐181c was downregulated in HCV patients compared with controls that disagrees with our finding 30,31 . This discrepancy between our result and others regarding miR‐181c may occurred because the other studies included patients infected with genotype‐1a and genotype‐2a HCV that have specific genome.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, previous findings showed that the maximum rate of gluconeogenesis is approached at glucose concentrations under 5 mM, whereas high glucose levels inhibit gluconeogenesis (40,41). Consistent with this observation, we did not detect any In addition, CHK2 activates p-CDK2/Cyclin A and cell cycle progression resulting in hepatocyte growth (53). Rb is hyperphosphorylated in liver cancer (54,55).…”
Section: O-glcnacylation On T378 Stabilizes Chk2 and Promotes Hepatomsupporting
confidence: 90%
“…HLE, HLF, and PLC/PRF5 (Japanese Collection of Research Bioresources, Japan) were also used as representative transformed hepatocytes of HCC. We also included THH generated in our laboratory [ 37 ]. Cell lines were cultured in DMEM or RPMI 1640 (Gibco BRL, NY) supplemented with 10% FBS (Gibco BRL, NY), 1% penicillin–streptomycin (Sigma-Aldrich, MO) antibiotic cocktail, and maintained at 37 °C in a humidified 5% CO2 incubator.…”
Section: Methodsmentioning
confidence: 99%